Drilling of hybrid composites comprising metallic and fiber laminates - Li, Hui Ling (2011)
With the maturing of lighter and stronger materials, fiber-reinforced composites and hybrid materials called Fiber Metal Laminates (FMLs) have become increasingly attractive to use as a replacement of the conventionally used aluminum alloys in aerospace components. In this project, carbon fiber-reinforced epoxy composites materials (CFRP) are used as the fiber reinforced layers while aluminums (Al) are used as the metallic layers.